A Survey Paper on Modern Online Cloud-Based Programming Platforms - Sreeram, N; Uday Kumar, V; Sridhara Rao, L (International Journal of Engineering and Technology, 2018)
Coding has more significance in any domain and there is availability of a variety of online cloud-based programming platforms. Programming involves several phases such as requirements identification, design solution, coding and testing. The main aim of any program is, it must meet the user requirements. Once programming is completed, the program must test against the user requirements. Hence there is need to understand and develop various test cases against user requirements specification to test the program. This paper gives an overview on how to identify, understand and resolve enforced test cases in programming over modern cloud-based compilers such as hackerrank, hacker earth, codechef etc.Â Â Â